Gone to Ground : A History of Environment and Infrastructure in Dar es Salaam - Brownell, Emily (Book collections on Project MUSE., 2020)
"Dar es Salaam, the largest city in Tanzania and the largest populated city in eastern Africa, was a changing urban landscape in the 1970s and 1980s. Gripped by an unfolding economic crisis and the fracturing of urban infrastructures, the citizens of Dar increasingly made their lives in transit between the city and its periphery, in order to find food, housing, and transportation. In doing so, they were turning to the ground to make life possible when they were either short on cash or other urban shortages broadly persisted. They exploited the coastal region's natural resources to shape their lives, relying on the city's outskirts to plant small shambas or to seek out building materials for their houses, goods to sell at markets, or charcoal for cooking the evening meal. Gone to Ground explores the ways in which the residents of Dar worked around or made do with what they could find, acquire, and grow in order to survive"--